Genomic features of attenuated Junín virus vaccine strain candidate - Goñi, Sandra Elizabeth (2006)
Junin virus strain Candid #1 was developed as a live attenuated vaccine for Argentine haemorrhagic fever. In this paper, we report the nucleotide sequences of L RNA of Candid #1 and examine the relationship to its more virulent ancestors Junin virus XJ#44 and XJ 13 (prototype) and other closely and distantly related arenaviruses. Comparisons of the nucleotide and amino acid sequences of L and Z genes of Candid #1 and its progenitor strains revealed twelve point mutations in the L polypeptide that are unique to the vaccine strain. These changes could be provisionally associated with the attenuated phenotype. In contrast, Z ORF was completely conserved among all strains.